1991
DOI: 10.2307/3889336
|View full text |Cite
|
Sign up to set email alerts
|

Basal Archosaurs: Phylogenetic Relationships and Functional Implications

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. ABSTRACT-Archosaurs first appeared in the Middle Triassic and within a short interval of time came to dominate all faunas of large vertebrates for the remainder of the Mesozoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
436
2
26

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(479 citation statements)
references
References 15 publications
15
436
2
26
Order By: Relevance
“…The possibility that basal members of all three major dinosaurian clades retained a quadrupedal hatchling stage is intriguing and cannot presently be excluded, but awaits further testing based on future discoveries. Similarly, the quadrupedal-to-bipedal shifts that occur in at least some taxa may recapitulate the evolutionary transition from quadrupedal basal archosaurs to bipedal avemetatarsalians that took place during the Early and Middle Triassic 29,30 , but this scenario will remain speculative until more information is available regarding the ontogeny of the early avemetatarsalian bipeds themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that basal members of all three major dinosaurian clades retained a quadrupedal hatchling stage is intriguing and cannot presently be excluded, but awaits further testing based on future discoveries. Similarly, the quadrupedal-to-bipedal shifts that occur in at least some taxa may recapitulate the evolutionary transition from quadrupedal basal archosaurs to bipedal avemetatarsalians that took place during the Early and Middle Triassic 29,30 , but this scenario will remain speculative until more information is available regarding the ontogeny of the early avemetatarsalian bipeds themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of numerical cladistic analyses in the mid 1980s crystallized support for both dinosaur monophyly and the hypothesis that birds evolved from theropod dinosaurs (e.g., Gauthier, 1986;Benton and Clark, 1988;Sereno, 1991a). Today, higher-level phylogenetic analyses continue to find robust support for dinosaur monophyly (e.g., Juul, 1994;Benton, 1999Benton, , 2004Sereno, 1999;Ezcurra, 2006;Langer and Benton, 2006;Irmis et al, 2007a;Brusatte et al, 2008a;Nesbitt et al, 2009b;Brusatte et al, 2010b;Nesbitt et al, 2010), although the exact characters diagnosing the dinosaur group continue to change as new fossils are found and old ideas are reinterpreted.…”
Section: Dinosauria: Diagnosismentioning
confidence: 99%
“…Over 50 characters have been cited as dinosaur synapomorphies in both pre-cladistic and cladistic studies (Bakker and Galton, 1974;Benton, 1984;Gauthier, 1986;Benton and Clark, 1988;Novas, 1989;Sereno, 1991a;Novas, 1992;Sereno and Novas, 1994;Novas, 1996;Benton, 1999;Sereno, 1999;Fraser et al, 2002;Langer and Benton, 2006;Irmis et al, 2007a;Nesbitt et al, 2009bNesbitt et al, , 2010Brusatte et al, 2010b). Potential dinosaur characteristics are distributed throughout the body.…”
Section: Dinosauria: Diagnosismentioning
confidence: 99%
“…For the phylogenetic relationships of pterosaurs, it has been suggested that Pterosauria (1) was the sister group of the Dinosauria (Sereno, 1991;Benton, 1999), (2) were basal archosauromorphs (Bennett, 1996), (3) or were members of the group Prolacertiformes (Peters, 2000). Recently, Benton (2007, 2008) provided new evidence to support the origin of the Pterosauria within Archosauria and we follow their definition here.…”
Section: Methodsmentioning
confidence: 99%
“…The isolated and three-dimensionally preserved cranial elements of this specimen provide a unique insight into the finer morphology and structure of some palatal bones of Dorygnathus. On the basis of the archosaurian affinities of the group (Sereno, 1991, Benton, 1999Hone and Benton, 2007), we adopted an extant phylogenetic bracket (''EPB,' ' Witmer, 1995a) approach to identify some of the isolated cranial elements and to reconstruct the palate of Dorygnathus. Comparison of the newly reconstructed palate of Dorygnathus with those of other pterosaur taxa helped to clarify some hitherto undescribed or misinterpreted bony elements and fenestrae in these taxa, and opened the way to propose possible evolutionary changes in the construction of the pterosaur palate.…”
mentioning
confidence: 99%